2015
DOI: 10.4236/psych.2015.61002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Indoor Play in Deaf Children: An Analysis of Play Behaviors

Abstract: Play is an important element of cognitive, social and language development. Most preschool classrooms provide opportunity for indoor play and studies are needed to improve indoor play contexts for all children, including deaf children. The present study documented and described the play behaviors of Ann, a four-year-old native American Sign Language (ASL) deaf child in an ASL/ English bilingual classroom. Ann engaged in various play behaviors, in different play centers, and with different play partners. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
(47 reference statements)
0
10
1
Order By: Relevance
“…Unlike the play behaviors of deaf and hard-of-hearing children described in previous studies (Esposito et al, 1989;Gatty, 1990), Musyoka (2015) suggested that this deaf child had play behaviors consistent with hearing children, especially play of hearing girls. The child engaged in more social, symbolic, and dramatic play when she played with children whom she deemed as friends than when she played with or near children that were identified as classmates (Musyoka, 2015). These findings suggest that when a deaf or hard-of-hearing child has access to a shared language of peers, play can be equally beneficial as it is with hearing children.…”
contrasting
confidence: 77%
“…Unlike the play behaviors of deaf and hard-of-hearing children described in previous studies (Esposito et al, 1989;Gatty, 1990), Musyoka (2015) suggested that this deaf child had play behaviors consistent with hearing children, especially play of hearing girls. The child engaged in more social, symbolic, and dramatic play when she played with children whom she deemed as friends than when she played with or near children that were identified as classmates (Musyoka, 2015). These findings suggest that when a deaf or hard-of-hearing child has access to a shared language of peers, play can be equally beneficial as it is with hearing children.…”
contrasting
confidence: 77%
“…Play partners are reported to influence the nature of play behavior, interactions and conversations (Doyle, Connolly, & Rivest, 1980;Hoff, 2010Hoff, , 2003Musyoka, 2015). Friendship in children's play is determined by observing children during play to see with whom they played (Marshall & McCandless, 1957;Ramsey, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Friendship in children's play is determined by observing children during play to see with whom they played (Marshall & McCandless, 1957;Ramsey, 1995). Doyle et al (1980) and Musyoka (2015) stress that peer familiarity has impact on the child's social interaction and cognitive level of play. They observed that in the presence of a familiar friend, the child demonstrated more social interactions and higher cognitive level of play.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations